Collective Exhibition for a Single Body : The Private Score : Vienna 2019 - Bal-Blanc, Pierre (Paris : Paraguay Press, 2019)
Adamciak, Milan ; Bratescu, Geta ; Daucikova, Anna ; Export, Valie ; Filko, Stano ; Gotovac, Tomislav ; Ivekovic, Sanja ; Jermolaewa, Anna ; Koller, Julius ; Kovanda, Jiri ; Ladik, Katalin ; Leung, Simon ; Miler, Karel ; Neagu, Paul ; Pelmus, Manuel ; Stembera, Petr ; Stilinovic, Mladen ; Stilinovic, Sven ; Tolj, Slaven ; Trbuljak, Goran
"The Private Score" is published by Paraguay on the occasion of the exhibtion "Exposition collective pour un corps individuel - La partition privée" at gb agency Paris from the 12th of October until the 5th of November 2019. This publication is co-produced in the context of Playground festival co-organized by M Leuven and STUK house for Dance, Image and Sound from 14th to 17th November 2019 with the supoort of the Kontakt Collection Vienna.
boek